Proceedings of SPE Annual Technical Conference and Exhibition 2004
DOI: 10.2523/90357-ms
|View full text |Cite
|
Sign up to set email alerts
|

Pushing the Limits of Hydraulic Fracturing in Russia

Abstract: TX 75083-3836, U.S.A., fax 01-972-952-9435. AbstractWe have established the concept of Unified Fracture Design (UFD) to maximize the dimensionless productivity index (J D ) following a hydraulic fracture treatment. For a given mass of proppant there is a specific dimensionless fracture conductivity, which we called the optimum, at which the J D becomes maximum. The Proppant Number is a seminal quantity unifying the propped fracture and the drainage volumes and the two permeabilities, those of the proppant pack… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 2 publications
1
5
0
Order By: Relevance
“…One of the clear messages is that the better the proppant the larger the indicated treatment should be and not the opposite as very conservative past practices have suggested. Similar findings have already been shown with a large set of parametric studies presented by Economides et al [2][3] , as well as in a field case study of almost a thousand hydraulic fracture treatments in Western Siberia in which Diyashev and Economides 4 provided a substantial experimental confirmation to the concept.…”
Section: Benchmarking Well Performance With the Unified Fracture Desisupporting
confidence: 82%
See 1 more Smart Citation
“…One of the clear messages is that the better the proppant the larger the indicated treatment should be and not the opposite as very conservative past practices have suggested. Similar findings have already been shown with a large set of parametric studies presented by Economides et al [2][3] , as well as in a field case study of almost a thousand hydraulic fracture treatments in Western Siberia in which Diyashev and Economides 4 provided a substantial experimental confirmation to the concept.…”
Section: Benchmarking Well Performance With the Unified Fracture Desisupporting
confidence: 82%
“…Even more, in some very progressive areas this design approach has been used to "push the limits" of today's practices in hydraulic fracturing. Economides, Demarchos et al [2][3] showed, for example, how relevant the mass of proppant is for the maximization of the productivity index. Diyashev and Economides 4 presented field case studies of almost a thousand hydraulic fracture treatments in Western Siberia, providing a very valuable experimental support for the UFD approach.…”
Section: Introductionmentioning
confidence: 99%
“…Using a set of constraints such as a limit of 1,000 psi net pressure during execution (affecting directly the resulting fracture width), a minimum hydraulic fracture width of at least 3 times the proppant diameter to prevent proppant bridging, and an injection time of no more than 24 hours; Economides et al (2004) developed a benchmarking graph for the maximum attainable J D for oil wells for a range of permeabilities, shown in Figure 3-6. This representation is significant because it suggests what extraordinary results can be achieved by pushing the limits of design and using large volumes of higher quality proppant, while still respecting operational and logistical constraints.…”
Section: Hydraulic Fracturing 87mentioning
confidence: 99%
“…5. This chart is split into three sections: (1) the initial fracture design criteria, (2) the injection test analysis, and (3) the redesign of the fracture treatment based on minifrac analysis and real-time main frac analysis.…”
Section: Design Processmentioning
confidence: 99%
“…Designing for performance required a change in tactics and an optimization mentality to achieve step-change results. 1,2 Production analysis suggested radical changes in fluids, breakers, job sizes, types, and tonnage of proppant, etc. In this paper, we discuss and compare the evolution of the stimulation practices and implementation of technology that matched performance to fracture design.…”
mentioning
confidence: 99%